EARLY DETECTION IN BOOSTING WHISTLEBLOWING INTEREST (Case Study at Pratama Tax Office of South Sidoarjo) - Dessy Dwi Fitra Nova; Tarjo Tarjo; Anita Carolina (Asia Pacific Fraud Journal, 2017)
ABTRACTThe main purpose of this study is to empirically examine and analyze the effect of early detection principles, comprising anonymous reporting, followed up reporting and reward system, on the encouragement of an individual interest in reporting fraud. The research was conducted at the Pratama Tax Office of South Sidoarjo. The samples used in this research were 53 respondents. Sample collection was done using saturation sampling technique. The results of this research show that followed up reporting has an effect on the encouragement of an individual interest in reporting fraud. In contrast, anonymous reporting and reward system have no effect on the encouragement of an individual interest in reporting fraud.